WHAT DRIVES CAPITAL STRUCTURE ? EVIDENCE FROM MANUFACTURING FIRMS IN INDONESIA - Malelak, Mariana Ing; Melvern, Myer; Gunawan, Nicholas Briliant (Universitas Nusa Cendana, 2025)
This study investigates the impact of profitability, liquidity, growth opportunity, and asset tangibility on the capital structure of manufacturing firms in Indonesia. This study employs the pecking order theory to examine data from 140 manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2024. The companies were chosen based on criteria such as having full financial statements, being listed before 2017, and not having negative equity. A total of 1,120 firm-year observations were analyzed using panel data regression with STATA. The findings indicate that profitability and liquidity have a significant negative impact on capital structure, while asset tangibility has a significant positive effect. However, growth opportunity does not have a significant effect, suggesting that expansion potential is not a primary factor in determining debt utilization among manufacturing firms. These findings support the pecking order theory and emphasize the importance of internal financial strength and asset structure in financing decisions. Companies are encouraged to maintain strong internal funding capabilities and manage debt prudently to ensure financial sustainability. Keywords: Capital Structure; Profitability; Liquidity; Growth Opportunity ; Asset Tangibility ; Manufacturing Sector